Blood Parasite Infection and Plumage Elaboration of Migratory and Resident Populations of the Common Yellowthroat - (:unkn) unknown (My University, 2016)
In birds, blood parasite diversity varies with latitude, seasonal changes, and habitat type. As a consequence, migratory populations of birds have greater exposure to parasites during their annual cycle than resident populations. Parasite infections may negatively affect the health of individuals which could, in turn, affect the development of elaborate plumage ornaments. We compared migratory (Wisconsin) and resident (Florida) populations of common yellowthroats (Geothlypis trichas) to test whether migratory birds in Wisconsin have more prevalent, intense and diverse infections of blood parasites and subsequently less elaborate ornamentation than their resident counterparts in Florida. As predicted, we found higher prevalence, intensity and diversity of blood parasites in Wisconsin than Florida birds. In terms of ornamentation, we found that Wisconsin males had brighter plumage in the yellow and ultraviolet spectra. These results demonstrate that blood parasite infection and plumage elaboration both differ between conspecific populations, possibly because of differences in migratory behavior.
Keywords: Common Yellowthroat; Migration; Ornamentation; Parasitism; Plumage